# Prove that (sin 3x + sin x) sin x + (cos 3x – cos x) cos x = 0

To Prove: (sin 3x + sin x) sin x + (cos 3x – cos x) cos x = 0

Formulas to use:  Proof:

Replacing x with 3x and y with x in the formula, we get- sin 3x + sin x = 2 sin 2x cos x …(1)

Similarly,

We know that Replacing x with 3x and y with x, we get- cos 3x - cos x = -2 sin 2x sin x …(2)

Now,

L.H.S = (sin 3x + sin x) sin x + (cos 3x – cos x) cos x

Putting the values obtained from equations 1 and 2 we get,

= (2 sin 2x cos x) sin x + (-2 sin 2x sin x) cos x

= 2 sin 2x cos x sin x - 2 sin 2x sin x cos x

= 0

= R.H.S

Hence, L.H.S = R.H.S…Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Conditional Identities31 mins  Trigonometric Functions - 0568 mins  Trigonometric Functions - 0152 mins  Graphs of trigonometric ratios | Trigonometric Identities39 mins  Quiz on Graph of Trigonometric Ratios40 mins  Trigonometric Functions - 0366 mins  Trigonometric Functions - 0658 mins  Trigonometric Series45 mins  Interactive Quiz on trigonometric ratios & identities73 mins  Trigonometric Functions - 0268 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 